ANALISIS DAMPAK TAYANGAN YOUTUBE TERHADAP PERKEMBANGAN MORAL ANAK USIA DINI - Mudianti, Haya; Cahyo, Edo Dwi (Al Athfal : Jurnal Kajian Perkembangan Anak dan Manajemen Pendidikan Usia Dini, 2023)
Moral development in early childhood is something that can uphold human values that are comprehensive so that they develop in society in accordance with the principles of justice, equality and mutual acceptance in their environment. Poor moral development can be caused by watching YouTube shows, such as politeness, discipline, responsibility, and honesty. The research method used in writing this scientific work is descriptive qualitative method. By using data collection techniques through observation, interviews and documentation. YouTube shows have an impact on children's moral development, namely Negative Impact: children like to Prank / lie, lack of discipline, lack of politeness towards teachers, lack of responsibility in doing assignments. Positive impact: children want to forgive each other, help each other, behave honestly, and maintain personal hygiene.